Requirement Model for CIAC Services Feedback System (CSFS) - Abdulwahid, Eissa Hamood (2012)
The universities may have an edge on the candidate’s competition, each strives to be a world recognized educational institution therefore Universiti Utara Malaysia is striving to keep hold of its global vision through the Centre for International Affairs & Cooperation (CIAC) department which is in charge of this mission. Services provided by the CIAC such as visa, accommodation and transportation are very important for the improvement of the academic and administrative quality and excellence in the education in Universiti Utara Malaysia. A requirement model for CIAC services feedback system based on the perspective of the students is developed to provide the CIAC’s decision-makers a wealth of valuable information about the response levels of the students regarding the critical services provided by the university. This requirements were gathered and developed in order to come out with a system that can perform survey easily, cost- effectively, time shortly with reports in the form of charts, graphs without needs of using data analysis tools. The collected requirements are verified and validated using a prototype to confirm that it fulfills the client needs and specifications. Rational Unified Process (RUP) methodology was adopted in order to fulfill the objectives.